Sickle Cell Disease: Thoughts for India From the Jamaican Cohort Study - Serjeant, Graham R. (Frontiers in Medicine, 2021)
The sickle cell gene in India represents a separate occurrence of the HbS mutation (the Asian haplotype), which has occurred against a genetic background characterised by high levels of fetal haemoglobin and widely varying frequencies of alpha thalassaemia. These features, which tend to inhibit sickling, change the expression of the disease, which, in India, may be further modified by poor nutrition, malaria and other infections, and limited public health resources. Sickle cell disease in Jamaica is predominantly of African origin (the Benin haplotype) and faces some similar challenges. This review assesses similarities and differences between disease expression in the two countries and seeks to explore lessons from Jamaica, which may be relevant to Indian health care. In particular, it addresses common causes of hospital admission as detailed from Indian clinical experience: anemia, bone pain crisis, and infections.